Cancer of the Transverse Colon: Comparison of Extended Right or Left Hemicolectomy versus Transverse Colectomy - Coco, Danilo; Leanza , Silvana (Open Access Macedonian Journal of Medical Sciences, 2020)
The transverse colon is the part of colon between right and left colon from right flexure to splenic flexure. Standard surgical treatment involves either extended colectomy (EC) or transverse colectomy (TC), depending on the location of the tumor. The aim of the present study was to compare anastomotic leakage, hospital stay, operative time, overall complications rate, harvested nodes overall survival, and disease-free survival comparing EC versus TC.